Effects of Glass Powder as a Supplementary Cementitious Material on the Performance of High Strength Mortars - Tarassoly, Amir Reza (Eastern Mediterranean University EMU, 2016)
Concrete, is the most widely used engineering material in construction. Since around 11 billion tons of concrete is used each year all over the world, considerable amount of cement is required for its production. This results in high production of carbon dioxide which is one of the main reasons of global warming. Therefore, in the last few years, there is a growing interest in using waste pozzolanic admixtures as a supplementary cementitious material. Using these kind of admixtures as a part of cement replacement reduces the air pollution, cost and also enhances some properties of mortars and concretes. Among the other waste natural pozzolans, glass powder becomes important due to its high content of silica, availability and cost. These motivate lots of researchers to evaluate the effects of glass powder as a cement replacement material. In this study, effects of three different types (colors) of glass powders with different quantities used as cement replacement on the workability and mechanical properties of high strength mortars were evaluated. For this purpose, the flow table test for workability, flexural and compressive strength tests, modulus of elasticity measurement, rapid chloride test for permeability were performed to determine the effects of water binder ratio on high strength mortars performance. Moreover, the effect of curing temperature on the performance of high strength mortars modified with glass powders was also investigated. Finally, comparison is done between the results of control, silica fume and glass powder specimens. It is important to note that glass powder addition as a pozzolanic material has a considerable influence on compressive strength and permeability at low water binder ratio specimens under high curing temperature. Keywords: glass powder, curing temperature, water-binder ratio, workability, compressive and flexural strength, modulus of elasticity, permeability

ÖZ: Beton, yapılarda en yaygın kullanılan yapı malzemesidir. Her yıl, dünya genelinde yaklaşık olarak 11 milyon ton beton üretilmektedir. Bu durumda ciddi miktarda çimento üretimi gerekmekte ve gerçekleştirilmektedir. Yüksek miktarda karbondioksit salınımına yol açan çimento üretimi, küresel ısınmaya yol açan en önemli sebeplerden birini oluşturmaktadır. Son yıllarda; çimento kullanımını azaltmak için, pozolanik özelik taşıyan atık malzemelerin çimentonun bir kısmının yerine kullanımı yoluna gidilmiştir. Bu tip katkı malzemelerinin kullanımı ile hem karbondioksit salınımının yol açtığı hava kirliliği azalmış olacak hem de daha az çimento kullanılacağından beton fiyatı düşecektir. Aynı zamanda, harç veya betonun bazı özeliklerinde de iyileşmeler olmacaktır. Öğütülmüş cam tozu, yüksek miktarda silis içerdiğinden, ucuz olduğundan ve de kolay bulunduğundan dolayı diğer pozolanik atık malzemelerin yanında en uygun olarak tercih edilmektedir. Atık cam tozunun bu olumlu özelikleri, araştırmacıların bu konuya ilgi duymalarına ve de cam tozunun kısmen çimentonun yerine kullanılması halinde betonun özeliklerinin nasıl değiştiği konusunda araştırma yapmalarına yol açmıştır. Bu çalışmada; üç farklı tipte (renkte) öğütülmüş cam tozu farklı miktarlarda olmak üzere çimentonun yerine kullanılmış ve de üç farklı tipte üretilmiş olan yüksek dayanımlı harçların işlenebilirlik,ve de mekanik özeliklerinin nasıl etkilendiği incelenmiştir. Bu deneysel çalışmada, su – bağlayıcı malzeme oranı ve farklı tip ve miktarlardaki cam tozunun yüksek dayanımlı harçlar üzerindeki etkisini tesbit etmek için; akma tablası işlenebilirlik, eğilme ve basınç dayanımı, elastic modulus ve de geçirimlilik deneyleri tüm numuneler için gerçekleştirilmiştir. Bunların yanısıra, üç farklı kür sıcaklığının yüksek dayanımlı harçlar üzerindeki etkisi tüm numuneler için araştırılmıştır. Sonuç olarak, kontrol, silis dumanı ve de cam tozu numunelerinden elde edilen sonuçlar kıyaslanmıştır. Burada belirtilmelidir ki; düşük su – bağlayıcı malzeme oranı ve de yüksek kür sıcaklığında, cam tozunun pozolanik atık malzeme olarak çimentonun yerine (kısmi) kullanılması; harcın basınç dayanımı ve de geçirimliliğini önemli ölçüde etkilemiştir. Anahtar Kelimeler: cam tozu, kür sıcaklığı, su/bağlayıcı, işlenebilirlik, eğilme ve basınç dayanımı, elastic modulus, geçirimlilik.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assist. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering; Construction Engineering-Supplementary Cementitious Materials-Glass Powder; Glass Powder-Cement Replacement Material; Glass powder; curing temperature; water-binder ratio; workability; compressive and flexural strength; modulus of elasticity; permeability